Overexpression of arogenate dehydratase reveals an upstream point of metabolic control in phenylalanine biosynthesis. (9th September 2021) - Yoo, Heejin; Shrivastava, Stuti; Lynch, Joseph H.; Huang, Xing‐Qi; Widhalm, Joshua R.; Guo, Longyun; Carter, Benjamin C.; Qian, Yichun; Maeda, Hiroshi A.; Ogas, Joseph P.; Morgan, John A.; Marshall‐Colón, Amy; et al.
SUMMARY: Out of the three aromatic amino acids, the highest flux in plants is directed towards phenylalanine, which is utilized to synthesize proteins and thousands of phenolic metabolites contributing to plant fitness. Phenylalanine is produced predominantly in plastids via the shikimate pathway and subsequent arogenate pathway, both of which are subject to complex transcriptional and post‐transcriptional regulation. Previously, it was shown that allosteric feedback inhibition of arogenate dehydratase (ADT), which catalyzes the final step of the arogenate pathway, restricts flux through phenylalanine biosynthesis. Here, we show that in petunia ( Petunia hybrida ) flowers, which typically produce high phenylalanine levels, ADT regulation is relaxed, but not eliminated. Moderate expression of a feedback‐insensitive ADT increased flux towards phenylalanine, while high overexpression paradoxically reduced phenylalanine formation. This reduction could be partially, but not fully, recovered by bypassing other known metabolic flux control points in the aromatic amino acid network. Using comparative transcriptomics, reverse genetics, and metabolic flux analysis, we discovered that transcriptional regulation of the d ‐ribulose‐5‐phosphate 3‐epimerase gene in the pentose phosphate pathway controls flux into the shikimate pathway. Taken together, our findings reveal that regulation within and upstream of the shikimate pathway shares control over phenylalanine biosynthesis in the plant cell. Significance Statement: An increase in phenylalanine levels is a frequent target of metabolic engineering strategies for efficient production of phenylalanine‐derived metabolites. Phenylalanine is produced predominantly in plastids via the shikimate pathway and is subject to complex transcriptional and post‐transcriptional regulation, which occurs not only within the pathway but also upstream in the pentose phosphate pathway.